Antimicrobial and antioxidant properties of the woody endocarp of native and commercial walnuts from Argentina = Propiedades antimicrobianas y antioxidantes del endocarpio leñoso de nogales nativos y comerciales de Argentina - Orce, Ingrid Georgina; Lencina, Sibila Ivonne; Furque, Gabriela Inés; Lorenzo, Emilia; Rodriguez Garay, Gretel Narda Cecilia; Pereyra, Fiamma; Alberto, María Rosa; Gomez Kamenoplsky, Patricia Elizabeth; Arena, Mario Eduardo (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2025)
Juglans australis is a tree from the Juglandaceae family found in the southernmost region of America. Its small edible nuts are not commercialized, and their bioactive characteristics are unknown. This study first reports the antioxidant, antiradical, and antibacterial activity of extracts from this native walnut against phytopathogenic bacteria and compared with its commercial counterpart, J. regia L. Different extracts from the woody endocarp (shells) were obtained using methanol and ethyl acetate. Methanolic extracts significantly inhibited phytopathogenic growth at all concentrations tested (0.1, 1, and 10 mg/mL). The best activity was reported against Xanthomonas. Highest total phenolics and the most significant antioxidant activity were determined in methanolic extracts (TPC: 121 mg gallic acid equivalent (GAE)/g of dried peel, FRAP: 58.6 mmol Trolox/100 g of peel dried and 9.7 mM Trolox/100 g of dried peel). Extracts from both species demonstrated congruent patterns. Gallic acid was the most abundant compound in the methanolic extract. However, extracts demonstrated superior efficiency, suggesting a potential synergistic effect among their components. Antioxidant and antimicrobial activity of methanolic extracts against Xanthomonas make them potential control agents.